Treatment of Grade III furcation involvement in upper molars: Case Series with 2-16-year follow-up - Ferreira, Camila [UNESP]; Fátima Pedroso, Juliana [UNESP]; Silva Lima, Victória [UNESP]; Souza Ramos, Tatiane [UNESP]; Melo Filho, Antonio [UNESP]; Neves Jardini, Maria [UNESP] (Wolters Kluwer, 2020)
Frequently, the clinicians are addressed to decide between the preservation of Grade III furcation molar and the implant replacement, due to the increased access among the population to this therapy over the years and high success rate of the osseointegrated implants. This case series presents clinical and radiographic data collected from 10 patients who underwent 13 root amputations for the treatment of degree Grade III furcation in maxillary molars with follow-up until 16 years. The results showed improvements in probing depth, bleeding on probing, and radiographic aspects. The follow-up time indicates that root amputation is an effective long-term treatment solution, especially when the patient's local, systemic, or financial conditions make it difficult or impossible to implant placement.
Keywords: Follow-up studies; furcation involvement; periodontal surgery; root-resective therapy; upper molars